Manuskrip Beraksara Jawi Pada Khazanah Pustaka EAP British Library - Sulistiyo, Rozib; Sani, Amilda; Rusli, Risan (Universitas Cokroaminoto Yogyakarta, 2023)
Jawi script is Arabic/hijaiyah letters with 6 additional letters as local modifications which -when read or pronounced- form Malay words/sentences. This Jawi script is proof of the influence of Islam in the archipelago. This study is historical research employing literature analysis examining the Jawi script collection within the digital library provided by the Endangered Archives Program (EAP) Riau manuscripts: The Gateway to The Malay Intellectual World (EAP153). The data obtained was then analyzed qualitatively through historiography descriptive analysis. The data was then discussed by comparing with other literacy sources such as journals, books and internet sources. Malay manuscripts stored in the British Library EAP library & Linggam Cahaya Library consist of 454 manuscripts including 65 (14%) written in Dutch, 30 (6.6%) written in Indonesian, 3 (0.7%) written in Arabic, 2 (2) 0.4%) written in English and 353 Jawi manuscripts (78%) and 118 bi-lingual literature collections. Based on the Jawi manuscripts provided in the EAP British Library collection and that of Linggam Cahaya Library, it can be understood that the use of Jawi writing provides an overview of the socio-cultural conditions of Malay at the time. It is also revealed that there had been ups and downs in the use of Jawi script. In the 19th century Jawi writing was the government official script, the most mastered script by the community, a sign of identity and a resistance symbol against colonialism. The prestige of Jawi script began to decline since school system spread and the use of Latin script in the schooling world started as the impact of the ethical politics of 1901.